Correlation among Symptomatic Presentation, Ultrasound Imaging, and Surgical Findings in Ovarian Neoplasms (Community Based Medical Journal, 2026)
There is a wide range of gynecological disorders with ovarian neoplasms that are clinically heterogeneous and have an obscure presentation, making early diagnosis difficult. The association of the clinical presentation with ultrasonographic findings and intraoperative findings are critical determinants in planning surgical management. A prospective, observational study was conducted in the Department of Obstetrics & Gynaecology, Community Based Medical College, Bangladesh (CBMC,B) Hospital, Mymensingh, Bangladesh, between June and December of 2024, to observe correlation among symptomatic presentation, ultrasound imaging, and surgical findings in ovarian neoplasms. Our study included 60 patients with ovarian neoplasms. Sociodemographic, clinical, menstrual and reproductive characteristics, use of contraceptives, ultrasound findings and results from laparotomy were recorded. 30% of the patients were young adults 31-40 years and 50% were in middle class social economic status. The presenting symptoms in the present study were predominantly abdominal mass (75%). 78.3% of ovarian tumors were found benign histopathogically, while 21.7% were malignant. Patients’ symptoms had no association with USG findings (p>0.05), while ultrasonographic findings were in high agreement with laparotomy features (kappa=0.82, p40 years (p=0.01). The diagnostic performance of ultrasound in differentiating benign from malignant tumors demonstrated 76.9% sensitivity, 95.7% specificity, PPV of 83.3%, and NPV of 93.8%, with overall diagnostic accuracy of 91.7%. Integration of clinical, radiological and surgical features improves the diagnostic accuracy and influences the appropriate treatment for ovarian neoplasia.  CBMJ 2026 January: vol. 15 no. 01 P:174-182